Spirocyclic replacements for the isatin in the highly selective, muscarinic M(1) PAM ML137: the continued optimization of an MLPCN probe molecule - Poslusney, Michael S. (2013)
This Letter describes the further optimization of an MLPCN probe molecule (ML137) through the introduction of 5- and 6- membered spirocycles in place of the isatin ketone. Interestingly divergent structure-activity relationships, when compared to earlier M(1) PAMs, are presented. These novel spirocycles possess improved efficacy relative to ML137, while also maintaining high selectivity for the human and rat muscarinic M(1) receptor subtype.